Investigating the Effect of Brand Experience and Service Quality on Brand Loyalty mediated by Brand Trust in Travel Umroh Al Madinah Mutiara Sunnah Kediri City - Muttaqien, Zaenul; Sudarmiatin; Wardana, Ludi Wishnu (Asian Journal of Management Analytics, 2023)
This study analyses the effect of brand experience and service quality on brand loyalty mediated by brand trust. This type of research is explanatory research and primary data collection using a questionnaire. The sampling technique used stratified proportionate random sampling method. The number of samples was 127 respondents who were Umrah pilgrims of PT Al Madinna Mutiara Sunnah. The data was processed using SmartPLS 3.0 software.  The results showed that Brand Experience and Service Quality each had a significant effect on brand trust. Brand Experience has a significant effect on brand loyalty, while service quality has no significant effect on brand loyalty. Brand trust significantly mediates the relationship between brand experience or service quality variables on brand loyalty.